Respuesta :
Answer:
B. -5
D. -3
Step-by-step explanation:
4x² + 32x + 60 = 0
Factor left side of equation.
4(x + 3)(x + 5) = 0
Set factors equal to 0
x + 3 = 0
x = -3
x + 5 = 0
x = -5
The solution is x = -3 or x = -5
Answer:
B and D
Step-by-step explanation:
Given
4x² + 32x + 60 = 0 ( divide all terms by 4 )
x² + 8x + 15 = 0
Consider the factors of the constant term (+ 15) which sum to give the coefficient of the x- term (+ 8)
The factors are + 5 and + 3 , since
5 × 3 = 15 and 5 + 3 = 8 , thus
(x + 5)(x + 3) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 5 = 0 ⇒ x = - 5 → B
x + 3 = 0 ⇒ x = - 3 → D